Gambaran Pemeriksaan CRP pada Perokok Berat Pekerja Konveksi â€œXâ€ - Fitrianingsih Fitrianingsih; Suparyati Suparyati; Imam Ardiyansyah (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
A convection worker is any person who works by receiving wages or other forms of remuneration in a place specially made to produce merchandise or jeans and apparel. Heavy smokers are people who smoke and immediately smoke cigarettes or people who smoke more than 20 cigarettes per day. Elevated levels of CRP associated with tobacco use Examination CRP is an acute phase protein that is formed in the liver due to an inflammatory process or infection. This study aims to determine the description of CRP in heavy smokers of convection workers